2016
DOI: 10.1038/srep24944
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets of Chinese herbs: a clinical study of hepatoma based on network pharmacology

Abstract: Traditional Chinese medicine (TCM) has been used to treat tumors for years and has been demonstrated to be effective. However, the underlying molecular mechanisms of herbs remain unclear. This study aims to ascertain molecular targets of herbs prolonging survival time of patients with advanced hepatocellular carcinoma (HCC) based on network pharmacology, and to establish a research method for accurate treatment of TCM. The survival benefit of TCM treatment with Chinese herbal medicine (CHM) was proved by Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 51 publications
1
69
0
Order By: Relevance
“…DU145 cells were seeded into 96-well plates at a density of 1x10 4 cells/well and cultured with complete medium containing various concentrations of ursolic acid (0, 10, 20, 40 and 80 µM) for 24, 48 and 72 h. Following ursolic acid treatment, CCK-8 reagent was added to the cells and incubated for 4 h at 37˚C in an atmosphere of 5% CO 2 . Subsequently, the absorbance of each well was detected at 450 nm using a microplate reader (Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DU145 cells were seeded into 96-well plates at a density of 1x10 4 cells/well and cultured with complete medium containing various concentrations of ursolic acid (0, 10, 20, 40 and 80 µM) for 24, 48 and 72 h. Following ursolic acid treatment, CCK-8 reagent was added to the cells and incubated for 4 h at 37˚C in an atmosphere of 5% CO 2 . Subsequently, the absorbance of each well was detected at 450 nm using a microplate reader (Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, the use of Chinese herbs to treat tumors is achieving increasing recognition (4)(5)(6). Previous studies have reported that Traditional Chinese Medicine (TCM) has effects on androgen-dependent and -independent prostate carcinoma (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Further, TCM has a good analgesic effect, and can promote the restoration of bowel peristalsis and minimize abdominal distension and urinary retention [30,31]. A series of statistical analyses showed that 8 herbs are closely associated with tumor proliferation, metastasis, angiogenesis and apoptosis [32]. These analyses also demonstrated that the products containing Ginseng, Astragalus and Mylabris have the greater significant therapeutic effects on HCC [33].…”
Section: Treatment Of Hcc Using Tcm Alone or In Combination With Othementioning
confidence: 84%
“…Network pharmacology, proposed by Andrew L. Hopkins, clarifies the synergistic effects and the underlying mechanisms of multi-component and multi-target agents by analyzing various networks of complex and multilevel interactions [15,16]. This method has been widely applied in systematic understanding of the mechanisms of herbal formula [7,17,18]. For example, it was used to identify 1327 targets of 673 compounds from nine herbs involved in Fc epsilon RI signaling pathway and regulation of immunoglobulin production from a Chinese herb formula on rheumatoid arthritis [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was used to identify 1327 targets of 673 compounds from nine herbs involved in Fc epsilon RI signaling pathway and regulation of immunoglobulin production from a Chinese herb formula on rheumatoid arthritis [7]. Gao et al ascertained molecular targets of herbs prolonging survival time of patients with advanced hepatocellular carcinoma (HCC) based on this method [18]. …”
Section: Introductionmentioning
confidence: 99%